PENGEMBANGAN UKBM BERBASIS IDENTIFIKASI KD DAN PENGAMBILAN SEMESTER PADA MATA PELAJARAN PJOK JENJANG SMA YANG MENGIMPLEMENTASIKAN SISTEM KREDIT SEMESTER - Vicky Adi Primajaya; Nanik Indahwati; Abdul Rachman Syam Tuasikal (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
This research is motivated by the implementation of SKS in schools. Schools that implement SKS are obliged to make UKBM. UKBM is an Independent Learning Activity Unit. In the form of learning media for companion students to understand a material. The researcher developed UKBM in PJOK subjects based on KD identification and semester taking. In the high school level PJOK subjects there are KD interrelated. Starting from KD in class X to KD in class XII. Researcher identified KD from the three grade levels. Next, the researcher made a draft of the KD identification model for the UKBM that was developed complete with the KD information originating and which semester should be taken. This will greatly support teaching and learning activities. In addition, the main purpose of SKS is that students can more freely determine their own learning speed by looking at the design of the model. UKBM Development Research Based on KD Identification and Semester Taking in High School Level PJOK Subjects that Implement Semester Credit System is conducted at SMAN 1 Tuban class X IPA 5, X IPA 7 and X IPS 1. Data obtained from the learning media questionnaire sheet in the form of quantitative data was used to analyze the advisability of developing the UKBM. The UKBM that was developed has received validation from three validators with three different backgrounds. One validator came from the Ministry of Education and Culture Republic of Indonesia SKS development team, one validator from the UNESA FIO lecturer and one validator from the Responsible person SKS of SMAN 1 Tuban. The results descriptive data analysis the percentage of learning media in the form of UKBM development showed a figure of 89%. This means that the UKBM Development occupies a very good predicate. Occupying a very good predicate means that the results of the development of UKBM are appropriate for use in learning. The results of the development of UKBM can be applied to high school level of PJOK subjects which implementing SKS.